Die Amateure und der General . The Amateurs and the General - Cramer, Helge (Helge Cramer Filmproduktion, 2005)
Verzio FF Submission The story of the destruction and rebirth of the Old Bridge of Mostar, a famous Muslim monument in the Balkans, as seen through the eyes of three men who spent their youth by the bridge, had been friends before the war, and have become enemies after. Praljak, Goran and Safet talk about life and war and the chances for peace in a war-torn country.